The product quality of Polish ski-resorts : a case study of Silesian skiers' requirements, satisfaction and complaints - Żemɫa, Michaɫ (Array, 2008)
Summary: Product quality is an issue widely discussed with regard to tourism destinations. Among many different approaches to service quality measurement implemented into tourism destinations research ground, two were chosen to be utilised in the case of Polish ski resorts, which were importance-performance grid (IPA) and Kano's model of customer satisfaction. Strengths and weaknesses of chosen methods were discussed and results achieved with those methods are well complementary. Due to some limitations of IPA presented in the literature the method was partially modified to ensure higher reliability of results. Consistency of received results proved usefulness of this approach. The Polish ski resorts market is a promising subject for analysis of product quality as, this issue has been rather ignored so far, both by practitioners and researchers. This was also mirrored in results achieved as generally the level of product quality was estimated to be quite low. Respondents were especially not satisfied with the high level of congestion exercised in ski resorts which lead to long queues. However they appreciated good access to Polish ski resorts. Interestingly enough, this low level of product quality is not discouraging for Polish skiers who are used to poor quality, and interested more in good access rather than high standard. Achieved results are influenced by the fact that inhabitants of only one Polish province located close to the mountains were interviewed. This fact might have increased the understanding of access, and diminished importance of additional services like accommodation or aprés-ski offers